PENGARUH JUMLAH WISATAWAN, JUMLAH HOTEL, PDRB TERHADAP PENERIMAAN PAJAK HOTEL - Putra, Arfend Adi; Azlina, Nur; Hasan, Mudrika alamsyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The aim of the research is to find out effect the number of tourist, number of Hotel PDRB that become the factors determining tax revenue of hotels in Pekanbaru City. The hotel tax is levied on the facilities or resort lodging services providers, which include motels, inns, cabins tourism, tourism guest house, guest house, lodging houses and the like, as well asa boarding house with the number of room more than 10 (ten). The results of this study are expected to provide input for the benefit and the Local Government of Pekanbaru, especially the Office of Financial Management. The research was a descriptive study. The methods of obtaining the data were observation and library research. The data were secondary data of time series from year 2007-2014. The method of analysis used multiple regression analysis with Hotel Tax revenue as the dependent variable and three independent variables, namely the number of tourists, the number of hotels and PDRB. The results reveal that the number of tourist, number of hotel and PDRB has a significant influence on hotel tax revenue. The percentage effect of the independent variable on the dependent variable is 94% while the remaining 6% were caused by other factors not included in the regression equations.Keywords:Tourist, Hotel, PDRB, and Hotel Tax Revenue